A bamboo-derived carbon fiber current collector, a preparation method and application thereof

CN122942328APending Publication Date: 2026-10-20CHONGQING LI DE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611011969.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-08
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

其中现有竹材碳纤维研究多用于锂离子电池负极材料,缺乏集流体应用研究

Benefits of technology

1、本发明采用竹源碳纤维进行湿法抄造与热压成型制备得到竹源碳纤维毡,再进行镀镍、镀铜和氧化,制备得到具有三维多孔结构的集流体;其中竹源碳纤维采用竹材作为主要碳源材料,通过高压均质处理最大程度保留了其天然孔隙骨架,在后续静电纺丝和碳化过程中,与PVP作为构建多孔结构的基础,相较于传统PAN基碳纤维,具有更高的孔隙率和更好的电解液浸润性,且竹材作为天然可再生资源,其生长周期短来源广泛且成本低廉,可以有效降低原材料成本,减少对化石资源的依赖,具有显著的经济性和环保性;另外竹材本身含有一定量的N、O杂原子,在碳化过程中无需额外引入杂原子源即可提升碳材料的电化学性能;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to the field of battery technology, specifically to a bamboo-derived carbon fiber current collector, its preparation method, and its application. The bamboo-derived carbon fiber current collector comprises the following preparation steps: bamboo slices are taken, ground, ball-milled, dried, and sieved; after homogenization, bamboo fibers are obtained; antimony-doped tin gel, bamboo fibers, polyacrylonitrile, and polyvinylpyrrolidone are mixed, and collected by electrospinning to obtain bamboo-derived fibers; these fibers are then subjected to hydrothermal treatment, pre-oxidation, and carbonization to obtain bamboo-derived carbon fibers; PE / PP composite fibers and bamboo-derived carbon fibers are mixed, filtered, and formed into pre-shaped carbon fiber felt; this is then hot-pressed to obtain bamboo-derived carbon fiber felt; finally, the bamboo-derived carbon fiber felt is subjected to palladium activation treatment, nickel plating pretreatment, and copper plating treatment; after treatment, it is immersed in an oxidation solution to obtain the bamboo-derived carbon fiber current collector. This invention studies bamboo-derived carbon fiber as a current collector, utilizing the unique natural structure of bamboo, and applies it to lithium batteries, exhibiting good cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, specifically to a bamboo-derived carbon fiber current collector, its preparation method, and its application. Background Technology

[0002] With the rapid development of new energy vehicles, consumer electronics, and energy storage power stations, the demand for high-energy-density and high-safety batteries is increasing. Lithium-ion batteries are considered the ideal choice for next-generation high-energy-density batteries due to their extremely high theoretical specific capacity and extremely low electrochemical potential. The current collector, as a crucial component of lithium-ion batteries, carries the positive and negative electrode active materials and facilitates electron collection and transport, directly determining the battery's internal resistance and affecting its lifespan and cycle stability. Traditional lithium-ion batteries typically use copper foil as the negative electrode current collector. While copper foil possesses excellent conductivity and mechanical strength, its high mass percentage in the battery limits the improvement of energy density. Furthermore, the smooth and dense surface of copper foil results in weak bonding between the active material and the current collector, making it prone to detachment during charge-discharge cycles. Its poor electrolyte wettability also hinders the rapid transport of lithium ions. With the increasing market demand for batteries with high energy density, high safety, and long cycle life, the development of novel lightweight current collector materials with high specific surface area and good electrolyte wettability has become a research hotspot. In recent years, researchers have actively explored alternatives to current collector materials. Besides traditional metal foils, porous metals, metal fibers, layered composite metals, and non-metallic conductive materials have all been extensively studied. Among these, carbon-based materials have become an ideal choice for current collector preparation due to their high specific surface area, excellent conductivity, good chemical stability, and tunable pore structure. Currently, the raw materials for carbon-based current collectors mainly include precursors such as polyacrylonitrile, phenolic resin, and pitch. These precursors are costly and have complex preparation processes, limiting the large-scale application of carbon-based current collectors. Meanwhile, the preparation of carbon-based current collectors using biomass materials is gradually becoming a research hotspot. Compared with traditional synthetic carbon sources, biomass materials have advantages such as wide availability, low cost, and renewability. Existing research on bamboo carbon fiber is mostly used for lithium-ion battery anode materials, lacking research on its application as a current collector.

[0003] Therefore, developing a current collector made from renewable biomass is of great significance for promoting the performance improvement of lithium batteries and green and sustainable development. Summary of the Invention

[0004] The purpose of this invention is to provide a bamboo-derived carbon fiber current collector, its preparation method, and its application, so as to solve the related technical problems existing in the prior art.

[0005] To achieve the above objectives, the present invention provides the following specific technical solutions: A method for preparing a bamboo-derived carbon fiber current collector includes the following preparation steps: Step 1: Take bamboo slices, grind, ball mill, dry and sieve, add deionized water for homogenization treatment, and then dry to obtain bamboo fiber; Step 2: After ultrasonically dispersing the antimony-doped tin gel in a mixed solvent, bamboo fiber, polyacrylonitrile and polyvinylpyrrolidone are added. After heating and stirring, electrospinning is performed to collect bamboo-derived fibers. These fibers are then subjected to hydrothermal treatment, pre-oxidation and carbonization to obtain bamboo-derived carbon fibers. Step 3: In the sheet forming cylinder, PE / PP composite fibers are placed in hydroxyethyl cellulose solution and stirred and dispersed. Bamboo source carbon fiber is then added and stirred and dispersed. The mixture is then filtered and sheet-formed to obtain pre-shaped carbon fiber felt. After natural drying, it is hot-pressed, cooled, and removed to obtain bamboo source carbon fiber felt. Step 4: After cutting the bamboo carbon fiber felt, place it in a palladium activation solution for activation treatment. After activation treatment, perform nickel plating pretreatment and copper plating treatment in sequence. After treatment, immerse it in an oxidation solution and finally take it out and dry it to obtain the bamboo carbon fiber current collector.

[0006] Preferably, the homogenization process in step 1 is carried out at a pressure of 1800 bar, and the homogenization is performed 5-6 times. Preferably, in step 1, the bamboo fiber is dried until the water content is 10-36%; Preferably, in step 2, the mass ratio of antimony-doped tin gel, bamboo fiber, polyacrylonitrile, and polyvinylpyrrolidone is (0.3-0.5):2:(1-1.6):2. Preferably, the preparation steps of antimony-doped tin gel are as follows: tin tetrachloride pentahydrate is placed in deionized water and stirred to obtain a tin precursor solution with a molar concentration of 0.6-0.8 mol / L; antimony trichloride is placed in hydrochloric acid solution and stirred to obtain an antimony precursor solution with a molar concentration of 2-2.5 mol / L; the tin precursor solution and the antimony precursor solution are mixed and stirred at a volume ratio of 1:(0.01-0.03) for 30-50 min, and then heated at 100℃ for 15-20 min to obtain antimony-doped tin gel; Preferably, the electrospinning process parameters in step 2 are: voltage of 13-15kV, liquid feed rate of 0.02-0.08mL / min, and receiving distance of 10-20cm; Preferably, the process parameters for hydrothermal treatment in step 2 are: treatment at 100-120℃ for 20-24 hours followed by drying; Preferably, the pre-oxidation process parameters in step 2 are: after treatment at 150-160℃ for 24 hours, the temperature is increased to 240-280℃ at 2℃ / min and held for 2-3 hours; Preferably, the carbonization process parameters in step 2 are: heating to 700-900℃ and holding for 2-4 hours under an argon atmosphere; Polyvinylpyrrolidone was removed through hydrothermal treatment and carbonization processes, and the pore structure of bamboo-derived carbon fibers was adjusted. Preferably, the mass ratio of PE / PP composite fiber to bamboo-derived carbon fiber in step 3 is 1:(2-2.5). Preferably, the hot pressing process parameters in step 3 are: temperature 150-160℃, pressure 5-8MPa, and hot pressing time 8-15min; Preferably, the areal density of bamboo-derived carbon fiber felt is 40-80 g / m². 2 The addition of PE / PP composite fibers provides adhesion to the fiber felt, and subsequent hot pressing improves the tightness between fibers while maintaining the porous structure inside the fiber felt. Bamboo-derived carbon fiber and PE / PP composite fibers are interwoven to form fiber nodes, constructing a disordered stacked fiber network.

[0007] Preferably, the palladium activation solution in step 4 comprises the following components at the following concentrations: 0.5 g / L PdCl2, 20 mL / L HCl, and deionized water as the solvent; the palladium activation treatment lasts for 10-12 min. Preferably, the process parameters for nickel plating pretreatment are as follows: the nickel plating solution includes the following components at the following concentrations: 40-50 g / L NiSO4·6H2O, 20-30 g / L NaH2PO2·H2O, 100-120 g / L NaC6H5O7·2H2O, and 50-60 g / L NH4Cl; the solvent is deionized water; the temperature of the nickel plating solution is 70-75℃; and the nickel plating pretreatment time is 20-40 min. Preferably, the copper plating process is as follows: The anode copper sheet and cathode copper sheet are placed in a copper sulfate solution, with the vertical distance between the anode and cathode set to 12-15 mm. The positive terminal of a DC power supply is connected to the anode copper sheet, and the negative terminal is connected to the cathode copper sheet. The pre-nickel-plated bamboo carbon fiber felt is placed on the cathode copper sheet, and a current of 0.5-0.8 A is applied. After electroplating for 30-50 minutes, the felt is removed and cleaned to obtain copper-plated bamboo carbon fiber felt. The copper sulfate solution consists of 50-60 g / L CuSO4 and 40-50 ml / L H2SO4. Preferably, the oxidation solution comprises the following components at the following concentrations: 40-50 g / L NaOH, 10-20 g / L K2S2O8, with deionized water as the solvent; the surface is treated by immersing in the oxidation solution for 15-30 min, thereby growing CuO nanostructures on the surface of the copper plating layer. The bamboo-derived carbon fiber current collector prepared by this invention can improve the overall performance of the negative electrode of lithium-ion batteries.

[0008] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention uses bamboo-derived carbon fiber to prepare bamboo-derived carbon fiber felt through wet papermaking and hot pressing, followed by nickel plating, copper plating, and oxidation to prepare a current collector with a three-dimensional porous structure. The bamboo-derived carbon fiber uses bamboo as the main carbon source material, and its natural porous framework is preserved to the maximum extent through high-pressure homogenization. In subsequent electrospinning and carbonization processes, it is used in conjunction with PVP as the basis for constructing the porous structure. Compared with traditional PAN-based carbon fiber, it has higher porosity and better electrolyte wettability. Furthermore, bamboo, as a natural renewable resource, has a short growth cycle, is widely available, and has low cost, which can effectively reduce raw material costs and decrease dependence on fossil resources, demonstrating significant economic and environmental benefits. In addition, bamboo itself contains a certain amount of N and O heteroatoms, eliminating the need to introduce additional heteroatom sources during carbonization to improve the electrochemical performance of the carbon material. 2. In the preparation of bamboo-derived carbon fiber by electrospinning bamboo fiber, antimony-doped tin gel is introduced to achieve the embedding of metal nanoparticles, further enriching the defect sites on the carbon fiber surface. This not only improves the intrinsic conductivity of the fiber but also provides certain active nucleation sites. In addition, antimony doping can suppress the volume expansion of tin, enhance structural stability, and improve the structural integrity of the electrode during cycling. The bamboo-derived carbon fiber felt is sequentially subjected to palladium activation, electroless nickel plating, copper electroplating, and alkaline oxidation. Among them, palladium activation provides reaction sites for subsequent electroless nickel plating, improving the density of the nickel layer deposition. Moreover, the aforementioned doped metal nanoparticles can optimize the surface active sites of carbon fiber, allowing for direct palladium activation without the need for traditional sensitization processes. Electroless nickel plating optimizes the interfacial bonding between the carbon fiber felt and the subsequent copper plating layer, and can also serve as a protective layer to prevent direct contact between carbon fiber and copper in the electrochemical environment, inhibiting corrosion. The copper plating layer finally fills the fiber gaps, forming a three-dimensional continuous conductive network, improving the overall current carrying capacity of the current collector, thereby enhancing the rate performance and cycle stability of the lithium-ion battery anode. Detailed Implementation

[0009] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. It should be understood that the embodiments described herein are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort should fall within the protection scope of the present invention; unless otherwise specified, the related raw materials are all conventional settings.

[0010] The preparation steps of bamboo fiber are as follows: take bamboo slices, grind, ball mill, dry and sieve, add deionized water for homogenization treatment, homogenize 6 times under a pressure of 1800 bar, and dry until the fiber water content is 24% to obtain bamboo fiber with an average particle size of 15μm. The palladium activation solution comprises the following components at the following concentrations: 0.5 g / L PdCl2, 20 mL / L HCl, and deionized water as the solvent; The preparation steps of the tin precursor solution are as follows: tin tetrachloride pentahydrate is placed in deionized water and stirred to obtain a tin precursor solution with a molar concentration of 0.6 mol / L; The preparation steps of the antimony precursor solution are as follows: antimony trichloride is placed in concentrated hydrochloric acid and stirred to obtain an antimony precursor solution with a molar concentration of 2 mol / L; the mass fraction of concentrated hydrochloric acid is 37%. The pre-plating nickel solution comprises the following components at the following concentrations: 40 g / L NiSO4·6H2O, 20 g / L NaH2PO2·H2O, 100 g / L NaC6H5O7·2H2O, and 50 g / L NH4Cl, with deionized water as the solvent. The copper sulfate solution consists of 50 g / L CuSO4 and 40 ml / L H2SO4; The oxidation solution comprises the following components at the following concentrations: 50 g / L NaOH, 10 g / L K2S2O8, with deionized water as the solvent; Polyacrylonitrile Mw=150000, polyvinylpyrrolidone Mw=1300000, PE / PP composite fiber is core-sheath type ES fiber, and the single filament diameter is 15μm; Example 1: This example provides a method for preparing a bamboo-derived carbon fiber current collector, specifically including the following steps: Step 1: Mix tin precursor solution and antimony precursor solution at a volume ratio of 1:0.03 and stir for 40 min. Then heat at 100℃ for 15 min to obtain antimony-doped tin gel. Place 0.5 g of antimony-doped tin gel in 40 mL of N,N-dimethylformamide and tetrahydrofuran mixed solvent at a volume ratio of 3:1 and sonicate for 30 min. Then add 2 g of bamboo fiber, 1.4 g of polyacrylonitrile and 2 g of polyvinylpyrrolidone. Stir at 60℃ for 12 h and then load into a syringe. Electrospinning is performed at 15 kV voltage, 0.08 mL / min injection rate and 15 cm receiving distance to obtain bamboo fiber. After hydrothermal treatment at 120℃ for 24 h, dry the fiber and treat it at 150℃ for 24 h. Then heat it to 240℃ at 2℃ / min and hold for 3 h. Finally, carbonize it at 800℃ for 3 h in an argon atmosphere to obtain bamboo carbon fiber. Step 2: In the sheet forming cylinder, PE / PP composite fibers are placed in a 1.2% (w / w) hydroxyethyl cellulose solution and stirred to disperse. Bamboo-derived carbon fiber is then added, with a PE / PP composite fiber to bamboo-derived carbon fiber mass ratio of 1:2.5. Stirring continues at 500 rpm for 30 minutes, followed by standing for 5 minutes. The mixture is then filtered to obtain pre-formed carbon fiber felt. After natural drying, it is placed in a flat vulcanizing machine and hot-pressed at 160℃ and 6MPa for 10 minutes. After cooling, it is removed to obtain a surface density of 60 g / m³. 2 Bamboo-based carbon fiber felt; Step 3: After cutting the bamboo carbon fiber felt to a diameter of 15mm, place it in palladium activation solution for activation treatment for 10min. After activation treatment, perform nickel plating pretreatment and copper plating treatment on the bamboo carbon fiber felt in sequence. After treatment, immerse it in an oxidation solution for 20min, take it out and dry it to obtain bamboo carbon fiber current collector. The process steps of nickel plating pretreatment are as follows: place the foamed nickel sheet in the pre-plating nickel solution, adjust the pH of the system to 8, and heat it to 75°C. When bubbles are generated on the surface of the foamed nickel sheet, add the activated bamboo carbon fiber felt and attach it tightly to the surface of the foamed nickel sheet. When a large number of bubbles are generated on the surface of the carbon fiber felt, remove the foamed nickel sheet, continue stirring and plating nickel for 25 minutes, clean and dry it to obtain the pre-plated nickel bamboo carbon fiber felt. The copper plating process is as follows: place the anode copper sheet and the cathode copper sheet into a copper sulfate solution, set the vertical distance between the anode and the cathode to 15mm, connect the positive terminal of the DC power supply to the anode copper sheet and the negative terminal to the cathode copper sheet, place the pre-nickel-plated bamboo carbon fiber felt on the cathode copper sheet, pass a current of 0.6A through it, and after electroplating for 35 minutes, take it out and clean it to obtain copper-plated bamboo carbon fiber felt.

[0011] Example 2: This example provides a method for preparing a bamboo-derived carbon fiber current collector, specifically including the following steps: Step 1: Mix tin precursor solution and antimony precursor solution at a volume ratio of 1:0.02 and stir for 50 min. Then heat at 100℃ for 20 min to obtain antimony-doped tin gel. Place 0.5 g of antimony-doped tin gel in 40 mL of N,N-dimethylformamide and tetrahydrofuran mixed solvent at a volume ratio of 3:1 and sonicate for 30 min. Then add 2 g of bamboo fiber, 1.6 g of polyacrylonitrile and 2 g of polyvinylpyrrolidone. Stir at 55℃ for 16 h and then load into a syringe. Electrospinning is performed at 15 kV voltage, 0.08 mL / min injection rate and 15 cm receiving distance to obtain bamboo-derived fiber. After hydrothermal treatment at 120℃ for 24 h, dry the fiber and treat it at 160℃ for 24 h. Then heat it to 240℃ at 2℃ / min and hold for 3 h. Finally, carbonize it at 900℃ for 2 h in an argon atmosphere to obtain bamboo-derived carbon fiber. Step 2: In the sheet forming cylinder, PE / PP composite fibers are placed in a 1.2% (w / w) hydroxyethyl cellulose solution and stirred to disperse. Bamboo-derived carbon fiber is then added, with a PE / PP composite fiber to bamboo-derived carbon fiber mass ratio of 1:2. Stirring continues at 500 rpm for 40 minutes, followed by standing for 5 minutes. The mixture is then filtered to obtain a pre-formed carbon fiber felt. After natural drying, it is placed in a flat vulcanizing machine and hot-pressed at 160℃ and 6MPa for 12 minutes. After cooling, it is removed, yielding a surface density of 65 g / m³. 2 Bamboo-based carbon fiber felt; Step 3: After cutting the bamboo carbon fiber felt to a diameter of 15mm, place it in palladium activation solution for activation treatment for 12min. After activation treatment, perform nickel plating pretreatment and copper plating treatment on the bamboo carbon fiber felt in sequence. After treatment, immerse it in an oxidation solution for 25min, take it out and dry it to obtain bamboo carbon fiber current collector. The process steps of nickel plating pretreatment are as follows: place the foamed nickel sheet in the pre-plating nickel solution, adjust the pH of the system to 8, and heat it to 75°C. When bubbles are generated on the surface of the foamed nickel sheet, add the activated bamboo carbon fiber felt and attach it tightly to the surface of the foamed nickel sheet. When a large number of bubbles are generated on the surface of the carbon fiber felt, remove the foamed nickel sheet, continue stirring and plating nickel for 25 minutes, clean and dry it to obtain the pre-plated nickel bamboo carbon fiber felt. The copper plating process is as follows: place the anode copper sheet and the cathode copper sheet into a copper sulfate solution, set the vertical distance between the anode and the cathode to 15mm, connect the positive terminal of the DC power supply to the anode copper sheet and the negative terminal to the cathode copper sheet, place the pre-nickel-plated bamboo carbon fiber felt on the cathode copper sheet, pass a current of 0.8A, and after electroplating for 40 minutes, take it out and clean it to obtain copper-plated bamboo carbon fiber felt.

[0012] Example 3: This example provides a method for preparing a bamboo-derived carbon fiber current collector, specifically including the following steps: Step 1: Mix tin precursor solution and antimony precursor solution at a volume ratio of 1:0.01 and stir for 30 min. Then heat at 100℃ for 15 min to obtain antimony-doped tin gel. Place 0.3 g of antimony-doped tin gel in 40 mL of N,N-dimethylformamide and tetrahydrofuran mixed solvent at a volume ratio of 3:1 and sonicate for 30 min. Then add 2 g of bamboo fiber, 1 g of polyacrylonitrile and 2 g of polyvinylpyrrolidone. Stir at 60℃ for 12 h and then load into a syringe. Electrospinning is performed at 15 kV voltage, 0.08 mL / min injection rate and 15 cm receiving distance to obtain bamboo fiber. After hydrothermal treatment at 120℃ for 24 h, dry the fiber and treat it at 160℃ for 24 h. Then heat it to 240℃ at 2℃ / min and hold for 3 h. Finally, carbonize it at 700℃ for 2 h in an argon atmosphere to obtain bamboo carbon fiber. Step 2: In the sheet forming cylinder, PE / PP composite fibers are placed in a 1.2% (w / w) hydroxyethyl cellulose solution and stirred to disperse. Bamboo-derived carbon fiber is then added, with a PE / PP composite fiber to bamboo-derived carbon fiber mass ratio of 1:2. Stirring continues at 500 rpm for 30 minutes, followed by standing for 5 minutes. The mixture is then filtered to obtain a pre-formed carbon fiber felt. After natural drying, it is placed in a flat vulcanizing machine and hot-pressed at 160℃ and 5MPa for 10 minutes. After cooling, it is removed to obtain a surface density of 50 g / m³. 2 Bamboo-based carbon fiber felt; Step 3: After cutting the bamboo carbon fiber felt to a diameter of 15mm, place it in palladium activation solution for activation treatment for 10min. After activation treatment, perform nickel plating pretreatment and copper plating treatment on the bamboo carbon fiber felt in sequence. After treatment, immerse it in an oxidation solution for 30min, take it out and dry it to obtain bamboo carbon fiber current collector. The process steps for nickel plating pretreatment are as follows: place the foamed nickel sheet in the pre-plating nickel solution, adjust the pH of the system to 8, and heat it to 75°C. When bubbles are generated on the surface of the foamed nickel sheet, add the activated bamboo carbon fiber felt and attach it tightly to the surface of the foamed nickel sheet. When a large number of bubbles are generated on the surface of the carbon fiber felt, remove the foamed nickel sheet, continue stirring and plating nickel for 30 minutes, and then clean and dry it to obtain the pre-plated nickel bamboo carbon fiber felt. The copper plating process is as follows: place the anode copper sheet and the cathode copper sheet into a copper sulfate solution, set the vertical distance between the anode and the cathode to 15mm, connect the positive terminal of the DC power supply to the anode copper sheet and the negative terminal to the cathode copper sheet, place the pre-nickel-plated bamboo carbon fiber felt on the cathode copper sheet, pass a current of 0.8A, and after electroplating for 45 minutes, take it out and clean it to obtain copper-plated bamboo carbon fiber felt.

[0013] Comparative Example 1: As a control experiment for Example 2, the difference is that oxidation is not performed in step 3; specifically, it includes the following steps: Step 1: Mix tin precursor solution and antimony precursor solution at a volume ratio of 1:0.02 and stir for 50 min. Then heat at 100℃ for 20 min to obtain antimony-doped tin gel. Place 0.5 g of antimony-doped tin gel in 40 mL of N,N-dimethylformamide and tetrahydrofuran mixed solvent at a volume ratio of 3:1 and sonicate for 30 min. Then add 2 g of bamboo fiber, 1.6 g of polyacrylonitrile and 2 g of polyvinylpyrrolidone. Stir at 55℃ for 16 h and then load into a syringe. Electrospinning is performed at 15 kV voltage, 0.08 mL / min injection rate and 15 cm receiving distance to obtain bamboo-derived fiber. After hydrothermal treatment at 120℃ for 24 h, dry the fiber and treat it at 160℃ for 24 h. Then heat it to 240℃ at 2℃ / min and hold for 3 h. Finally, carbonize it at 900℃ for 2 h in an argon atmosphere to obtain bamboo-derived carbon fiber. Step 2: In the sheet forming cylinder, PE / PP composite fibers are placed in a 1.2% (w / w) hydroxyethyl cellulose solution and stirred to disperse. Bamboo-derived carbon fiber is then added, with a PE / PP composite fiber to bamboo-derived carbon fiber mass ratio of 1:2. Stirring continues at 500 rpm for 40 minutes, followed by standing for 5 minutes. The mixture is then filtered to obtain a pre-formed carbon fiber felt. After natural drying, it is placed in a flat vulcanizing machine and hot-pressed at 160℃ and 6MPa for 12 minutes. After cooling, it is removed, yielding a surface density of 65 g / m³. 2 Bamboo-based carbon fiber felt; Step 3: After cutting the bamboo carbon fiber felt to a diameter of 15mm, place it in palladium activation solution for activation treatment for 12min. After activation treatment, perform nickel plating pretreatment and copper plating treatment on the bamboo carbon fiber felt in sequence. After the treatment is completed, take it out and dry it to obtain bamboo carbon fiber current collector. The process steps of nickel plating pretreatment are as follows: place the foamed nickel sheet in the pre-plating nickel solution, adjust the pH of the system to 8, and heat it to 75°C. When bubbles are generated on the surface of the foamed nickel sheet, add the activated bamboo carbon fiber felt and attach it tightly to the surface of the foamed nickel sheet. When a large number of bubbles are generated on the surface of the carbon fiber felt, remove the foamed nickel sheet, continue stirring and plating nickel for 25 minutes, clean and dry it to obtain the pre-plated nickel bamboo carbon fiber felt. The copper plating process is as follows: place the anode copper sheet and the cathode copper sheet into a copper sulfate solution, set the vertical distance between the anode and the cathode to 15mm, connect the positive terminal of the DC power supply to the anode copper sheet and the negative terminal to the cathode copper sheet, place the pre-nickel-plated bamboo carbon fiber felt on the cathode copper sheet, pass a current of 0.8A, and after electroplating for 40 minutes, take it out and clean it to obtain copper-plated bamboo carbon fiber felt.

[0014] Comparative Example 2: As a control experiment for Example 2, the difference is that PAN-based carbon fiber was used instead of the bamboo-derived carbon fiber prepared in this application. The PAN-based carbon fiber is model T700SC-12K; specifically, the following steps were included: Step 1: In the sheet forming cylinder, PE / PP composite fibers are placed in a 1.2% (w / w) hydroxyethyl cellulose solution and stirred to disperse. Then, PAN-based carbon fibers are added, with a mass ratio of PE / PP composite fibers to PAN-based carbon fibers of 1:2. Stirring is continued at 500 r / min for 40 min, followed by standing for 5 min. The mixture is then filtered to obtain pre-formed carbon fiber felt. After natural drying, it is placed in a flat vulcanizing machine and hot-pressed at 160℃ and 6 MPa for 12 min. After cooling, it is removed to obtain a surface density of 65 g / m³. 2 carbon fiber felt; Step 2: After cutting the carbon fiber felt to a diameter of 15mm, place it in palladium activation solution for activation treatment for 12min. After activation treatment, perform nickel plating pretreatment and copper plating treatment in sequence. After treatment, immerse it in an oxidation solution for 25min, take it out and dry it to obtain carbon fiber current collector. The process steps of nickel plating pretreatment are as follows: place the nickel foam sheet in the pre-plating nickel solution, adjust the pH of the system to 8, and heat it to 75°C. When bubbles are generated on the surface of the nickel foam sheet, add the activated carbon fiber felt and attach it tightly to the surface of the nickel foam sheet. When a large number of bubbles are generated on the surface of the carbon fiber felt, remove the nickel foam sheet, continue stirring and plating nickel for 25 minutes, clean and dry to obtain the pre-plated nickel carbon fiber felt. The copper plating process is as follows: place the anode copper sheet and the cathode copper sheet into a copper sulfate solution, set the vertical distance between the anode and the cathode to 15 mm, connect the positive terminal of the DC power supply to the anode copper sheet and the negative terminal to the cathode copper sheet, place the pre-nickel-plated carbon fiber felt on the cathode copper sheet, pass a current of 0.8 A, and after electroplating for 40 minutes, remove and clean to obtain copper-plated carbon fiber felt.

[0015] Comparative Example 3: As a control experiment for Example 2, the difference is that the bamboo-derived carbon fiber is not doped with antimony or tin; specifically, it includes the following steps: Step 1: In 40 mL of a mixed solvent of N,N-dimethylformamide and tetrahydrofuran (volume ratio 3:1), add 2 g of bamboo fiber, 1.6 g of polyacrylonitrile, and 2 g of polyvinylpyrrolidone. After stirring at 55 °C for 16 h, the mixture is loaded into a syringe and electrospun at a voltage of 15 kV, a feed rate of 0.08 mL / min, and a receiving distance of 15 cm. Bamboo-derived fibers are collected, hydrothermally treated at 120 °C for 24 h, dried, treated at 160 °C for 24 h, heated to 240 °C at a rate of 2 °C / min and held for 3 h, and then carbonized at 900 °C for 2 h under an argon atmosphere to obtain bamboo-derived carbon fibers. Step 2: In the sheet forming cylinder, PE / PP composite fibers are placed in a 1.2% (w / w) hydroxyethyl cellulose solution and stirred to disperse. Bamboo-derived carbon fiber is then added, with a PE / PP composite fiber to bamboo-derived carbon fiber mass ratio of 1:2. Stirring continues at 500 rpm for 40 minutes, followed by standing for 5 minutes. The mixture is then filtered to obtain a pre-formed carbon fiber felt. After natural drying, it is placed in a flat vulcanizing machine and hot-pressed at 160℃ and 6MPa for 12 minutes. After cooling, it is removed, yielding a surface density of 65 g / m³. 2 Bamboo-based carbon fiber felt; Step 3: After cutting the bamboo carbon fiber felt to a diameter of 15mm, place it in palladium activation solution for activation treatment for 12min. After activation treatment, perform nickel plating pretreatment and copper plating treatment on the bamboo carbon fiber felt in sequence. After treatment, immerse it in an oxidation solution for 25min, take it out and dry it to obtain bamboo carbon fiber current collector. The process steps of nickel plating pretreatment are as follows: place the foamed nickel sheet in the pre-plating nickel solution, adjust the pH of the system to 8, and heat it to 75°C. When bubbles are generated on the surface of the foamed nickel sheet, add the activated bamboo carbon fiber felt and attach it tightly to the surface of the foamed nickel sheet. When a large number of bubbles are generated on the surface of the carbon fiber felt, remove the foamed nickel sheet, continue stirring and plating nickel for 25 minutes, clean and dry it to obtain the pre-plated nickel bamboo carbon fiber felt. The copper plating process is as follows: place the anode copper sheet and the cathode copper sheet into a copper sulfate solution, set the vertical distance between the anode and the cathode to 15mm, connect the positive terminal of the DC power supply to the anode copper sheet and the negative terminal to the cathode copper sheet, place the pre-nickel-plated bamboo carbon fiber felt on the cathode copper sheet, pass a current of 0.8A, and after electroplating for 40 minutes, take it out and clean it to obtain copper-plated bamboo carbon fiber felt.

[0016] Test method: The negative electrode active slurry was coated onto the surface of the current collectors prepared in Examples 1-3 and Comparative Examples 1-3. After drying, electrolyte was dropped onto the surface, and then a Celgard 2325 separator, lithium sheet, stainless steel gasket, stainless steel spring sheet, and battery casing were sequentially covered to assemble a coin-type lithium-ion half-cell. After standing for 12 hours, charge-discharge cycles were performed with the voltage set to 0.002-3V and the charge-discharge rate set to 0.1C. The initial discharge capacity and the discharge capacity after 50 cycles were recorded. Then, a rate cycle test was performed, with 10 cycles each at the initial 0.1C and subsequent current rates of 0.2C and 0.5C, followed by a 10-cycle capacity retention test at 0.1C. The negative electrode active slurry was composed of carbon microspheres, conductive carbon black, styrene-butadiene rubber, and sodium carboxymethyl cellulose in a mass ratio of 93:3:2:2. The carbon microsphere loading in the lithium-ion half-cell was 8.5 mg / cm³. 2 .

[0017] Table 1

[0018] Conclusion: Based on the above test data, Example 2 exhibits the best overall performance. Comparative Example 1, as the control group, did not undergo oxidation, resulting in a lack of CuO structure on the copper plating surface, leading to a decrease in specific surface area and electrolyte wettability. Consequently, both initial discharge capacity and cycle stability decreased. Comparative Example 2, as the control group, used PAN-based materials instead of bamboo-derived carbon fibers. Due to the lack of active sites, the plating layer was uneven and discontinuous, resulting in a reduction in transport channels and a significant decrease in capacity. Comparative Example 3, as the control group, used materials without antimony and tin doping, lacking the conductivity enhancement effect of metal nanoparticles, and its test data were all lower than those of the examples.

[0019] For those skilled in the art, it is obvious that the present invention is not limited to the details disclosed in the exemplary embodiments described above. The present invention can be implemented in other specific ways without departing from its spirit and essential characteristics. Therefore, the foregoing embodiments should be considered exemplary rather than restrictive from any perspective. The scope of protection of the present invention is defined by the appended claims. Therefore, all variations falling within the meaning and scope of the equivalent elements of the claims should be attributed to the scope of the present invention.

Claims

1. A method for preparing a bamboo-derived carbon fiber current collector, characterized in that, The preparation steps include the following: Step 1: Take bamboo slices, grind, ball mill, dry and sieve, add deionized water for homogenization treatment, and then dry to obtain bamboo fiber; Step 2: After ultrasonically dispersing the antimony-doped tin gel in a mixed solvent, bamboo fiber, polyacrylonitrile and polyvinylpyrrolidone are added. After heating and stirring, electrospinning is performed to collect bamboo-derived fibers. These fibers are then subjected to hydrothermal treatment, pre-oxidation and carbonization to obtain bamboo-derived carbon fibers. Step 3: In the sheet forming cylinder, PE / PP composite fibers are placed in hydroxyethyl cellulose solution and stirred and dispersed. Bamboo source carbon fiber is then added and stirred and dispersed. The mixture is filtered and sheet-formed to obtain pre-formed carbon fiber felt. After natural drying, it is hot-pressed, cooled, and taken out to obtain bamboo source carbon fiber felt. Step 4: After cutting the bamboo carbon fiber felt, place it in a palladium activation solution for activation treatment. After activation treatment, perform nickel plating pretreatment and copper plating treatment in sequence. After treatment, immerse it in an oxidation solution and finally take it out and dry it to obtain the bamboo carbon fiber current collector.

2. The method for preparing a bamboo-derived carbon fiber current collector according to claim 1, characterized in that, The homogenization process in step 1 is carried out at a pressure of 1800 bar, and the homogenization is repeated 5-6 times; the drying process in step 1 is carried out until the water content of the bamboo fiber is 10-36%.

3. The method for preparing a bamboo-derived carbon fiber current collector according to claim 1, characterized in that, In step 2, the mass ratio of antimony-doped tin gel, bamboo fiber, polyacrylonitrile, and polyvinylpyrrolidone is (0.3-0.5):2:(1-1.6):

2. The preparation steps of the antimony-doped tin gel are as follows: tin tetrachloride pentahydrate is placed in deionized water and stirred to obtain a tin precursor solution with a molar concentration of 0.6-0.8 mol / L; antimony trichloride is placed in hydrochloric acid solution and stirred to obtain an antimony precursor solution with a molar concentration of 2-2.5 mol / L; the tin precursor solution and the antimony precursor solution are mixed and stirred at a volume ratio of 1:(0.01-0.03) for 30-50 min, and then heated at 100℃ for 15-20 min to obtain the antimony-doped tin gel.

4. The method for preparing a bamboo-derived carbon fiber current collector according to claim 1, characterized in that, The electrospinning process parameters in step 2 are: voltage 13-15kV, liquid feed rate 0.02-0.08mL / min, and receiving distance 10-20cm; the hydrothermal treatment process parameters in step 2 are: treatment at 100-120℃ for 20-24h followed by drying; the pre-oxidation process parameters in step 2 are: treatment at 150-160℃ for 24h, followed by heating to 240-280℃ at a rate of 2℃ / min and holding for 2-3h; the carbonization process parameters in step 2 are: heating to 700-900℃ and holding for 2-4h under an argon atmosphere.

5. The method for preparing a bamboo-derived carbon fiber current collector according to claim 1, characterized in that, In step 3, the mass ratio of PE / PP composite fiber to bamboo-derived carbon fiber is 1:(2-2.5); the hot-pressing process parameters in step 3 are: temperature 150-160℃, pressure 5-8MPa, and hot-pressing time 8-15min; the areal density of the bamboo-derived carbon fiber felt is 40-80g / m³. 2 .

6. The method for preparing a bamboo-derived carbon fiber current collector according to claim 1, characterized in that, In step 4, the palladium activation solution comprises the following components at the following concentrations: 0.5 g / L PdCl2, 20 mL / L HCl, and deionized water as the solvent; the palladium activation treatment lasts for 10-12 min; the process parameters for the nickel plating pretreatment are as follows: the nickel plating solution comprises the following components at the following concentrations: 40-50 g / L NiSO4·6H2O, 20-30 g / L NaH2PO2·H2O, 100-120 g / L NaC6H5O7·2H2O, 50-60 g / L NH4Cl, and deionized water as the solvent; the nickel plating solution temperature is 70-75℃; and the nickel plating pretreatment time is 20-40 min.

7. The method for preparing a bamboo-derived carbon fiber current collector according to claim 1, characterized in that, The copper plating process is as follows: Anode and cathode copper sheets are placed in a copper sulfate solution, with a vertical distance of 12-15 mm between the anode and cathode. The positive terminal of a DC power supply is connected to the anode copper sheet, and the negative terminal is connected to the cathode copper sheet. A pre-nickel-plated bamboo carbon fiber felt is placed on the cathode copper sheet, and a current of 0.5-0.8 A is applied. After electroplating for 30-50 minutes, the felt is removed and cleaned to obtain copper-plated bamboo carbon fiber felt. The copper sulfate solution consists of 50-60 g / L CuSO4 and 40-50 ml / L H2SO4.

8. The method for preparing a bamboo-derived carbon fiber current collector according to claim 1, characterized in that, The oxidation solution comprises the following components at the following concentrations: 40-50 g / L NaOH and 10-20 g / L K2S2O8, with deionized water as the solvent; the person is immersed in the oxidation solution for 15-30 minutes.

9. A bamboo-derived carbon fiber current collector prepared by the preparation method according to any one of claims 1-8.

10. The application of the bamboo-derived carbon fiber current collector as described in claim 9 in the assembly of lithium-ion batteries.